Integration of ICT To Improve Student Learning Achievement in Islamic Education - Rahmawati, Putri; Mustofa, Triono Ali (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2024)
ICT Integration in Islamic Education: Solutions to improve student achievement in Islamic education In the digital era, the importance of using information and communication technology (ICT) in the digital era through Islamic education cannot be denied. The advantages of using such technology are not only that it provides a lot of up-to-date information gathering but more importantly it also makes it easier to access, faster and flexible. The method I took in this research is a literature study with a qualitative approach where the purpose of this research is to find out more about the use of information and communication technology (ICT), especially in the field of Islamic education to improve student achievement. Because many education throughout Indonesia prioritize Islamic education. In today's digital era, information and communication technology (ICT) plays an important role in developing Islamic education. In addition, it has made many changes to Islamic education, especially in improving student achievement. This paper traces the roots of information and communication technology (ICT) processes in Islam to improve student achievement in the digital age. The result of this study is that information and communication technology (ICT) will provide more opportunities for optimal learning facilities that are still developing faster than expected. The challenge ahead as educators, namely the integration of information and communication technology (ICT) in Islamic education to improve student achievement, is not something that should be avoided, but alternative learning approaches that are a necessity in improving student achievement in Islamic education.